Refractory adult-onset Still disease treated by tocilizumab combined with methotrexate: A STROBE-compliant article. Issue 32 (August 2019) - Wang, Chun-yan; Guo, Shao-hua; Wang, Li-ping; Shen, Hai-li
Abstract : Abstract: Some patients have poor response to adult-onset Still disease (AOSD) traditional treatment, which easily recurs during the reduction of prednisone. We observed the efficacy and safety of tocilizumab combined with methotrexate (MTX) in the treatment of refractory AOSD, and to explore the possibility of reducing the dosage of tocilizumab after disease control. A total of 28 refractory AOSD cases who had an inadequate response to corticosteroids combined with at least 1 traditional immunosuppressive agent, and even large-dose prednisone could not relieve their conditions after recurrence, were selected in this study. They were treated with tocilizumab (intravenous 8 mg/kg) combined with MTX (oral 12.5 mg once a week). In detail, tocilizumab was firstly given every 4 weeks and after 6-month remission, it was then given every 8 weeks. Some items including body temperature, skin rash, joint swelling and pain, hepatosplenomegaly, blood routine, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), serum ferritin, and dosage of prednisone were observed before treatment as well as 2, 4, 8, 12, 24, 36, and 48 weeks after treatment. The adverse reactions occurring during the treatment were recorded. The body temperature was normal, the skin rash as well as joint swelling and pain disappeared, and laboratory indexes including CRP, ESR, white blood cell, neutrophilic granulocyte, platelet, hemoglobin, and ferritin were significantly improved after 8-week treatment (all P < .05). The clinical symptoms and laboratory indexes above mentioned were continuously improved 12, 24, 36, and 48 weeks after treatment. The mean dosage of prednisone was reduced from 71.4 ± 20.7 mg/day to 55.0 ± 11.1 mg/day after 2-week treatment, and to 3.3 ± 2.1 mg/day after 48-week treatment (all P < .05). Prednisone was discontinued in 5 cases after 36-week treatment and in 7 cases after 48-week treatment. No serious adverse reactions occurred during the treatment. Tocilizumab can rapidly and markedly improve the clinical symptoms and laboratory indexes and contribute to reduction and discontinuation of prednisone in refractory AOSD. The patients' conditions are stable after reduction or discontinuation of prednisone and the tocilizumab possesses good safety.